2018
DOI: 10.1002/adem.201800202
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Low Carbon Steels Obtained from the Martensitic State via Severe Plastic Deformation, Precipitation, Recovery, and Recrystallization

Abstract: The range of accessible microstructures from the combination of severe plastic deformation (SPD) and heat treatments of a low carbon steel martensite under various processing conditions is evaluated. SPD results in a temperature decrease for recrystallization and austenitization upon subsequent annealing. On the contrary, the precipitation of cementite takes place at higher temperatures after SPD. Whereas, a certain thermal stability is observed for subsequent processing, even low annealing temperatures have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[15] The degree of grain refinement is not only dependent on the corresponding SPD technique but also on the processing temperature. [16][17][18][19] Generally, the deformation temperature is preferred to be less than 0.3T m , where T m is the melting temperature in K, to predominantly achieve 70 to 80% of high-angle GBs (HAGB, GB misorientation >15°). [12,20] However, some metals and alloys cannot be processed at those temperatures owing to their limited workability.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The degree of grain refinement is not only dependent on the corresponding SPD technique but also on the processing temperature. [16][17][18][19] Generally, the deformation temperature is preferred to be less than 0.3T m , where T m is the melting temperature in K, to predominantly achieve 70 to 80% of high-angle GBs (HAGB, GB misorientation >15°). [12,20] However, some metals and alloys cannot be processed at those temperatures owing to their limited workability.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the methods to obtain refined grains mainly include the addition of rare earth elements (Liu et al, 2010) or large plastic deformation (Korznikov et al, 1994;Yanushkevich et al, 2016;Müller et al, 2019). However, economically, these two methods are not appropriate for mass production.…”
Section: Introductionmentioning
confidence: 99%
“…High-Pressure torsion has also been used to process low and medium-carbon steel, low alloyed, and mild steel (7,8,38,39,40) . The studies have shown the occurrence of elongated grains and the dissolution of carbide precipitates and other phase colonies such as pearlite and cementite.…”
mentioning
confidence: 99%